2020
DOI: 10.3390/pr8080894
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study on the Influence of Dodecyl Trimethyl Ammonium Bromide on the CH4 Adsorption of Coal

Abstract: The adsorption of dodecyl trimethyl ammonium bromide (DTAB) on coal can affect the wettability of coal and change the water absorption of coal. After DTAB treatment, the change in the CH4 adsorption capacity of coal is worth further study. To reveal the microscopic mechanism of the influence of DTAB on the CH4 adsorption capacity of coal, we employed the density functional theory (DFT) with the 6-311 G (d, p) basis set. DFT-based computations interpreted the adsorption process of CH4 and DTAB on coal molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Guanwen Lu studied adsorption models for different coal types and found that the most applicable models for raw coal, fission coal and flake coal were the Toth, L-F and D-A models (Lu et al, 2020). Through the study of the adsorption model, Liu Shuo found that the DA model can describe the adsorption features of coal well (Liu et al, 2020). As mentioned above, scholars have mainly focused on the consideration of single factors such as temperature or pressure, with little consideration given to the effect of pore structure.…”
mentioning
confidence: 99%
“…Guanwen Lu studied adsorption models for different coal types and found that the most applicable models for raw coal, fission coal and flake coal were the Toth, L-F and D-A models (Lu et al, 2020). Through the study of the adsorption model, Liu Shuo found that the DA model can describe the adsorption features of coal well (Liu et al, 2020). As mentioned above, scholars have mainly focused on the consideration of single factors such as temperature or pressure, with little consideration given to the effect of pore structure.…”
mentioning
confidence: 99%